Indicadores de desenvolvimento da atividade voluntária na Educação infantil: o jogo de papéis como atividade principal - Moraes, Marcela Cristina de (2018)
According to Historical-Cultural Theory, voluntary activity is a neoformation which appears at the end of pre-school age, becoming children aware of their actions and capable of controlling them. A delayed development of voluntary activity poses complications on their school life when they are not able to neither organize school activities nor focus attention. This research aims at assessing developmental indicators of voluntary activity, among 3-6 years-old children, from role play activity and structured and non-structured children´s play. The research was carried out in Brazil and in Mexico, having the following characteristics: in both countries participant observation with 3-6 years-old children in pre-school age was conducted. In Mexico, this research was carried out in a private school, and in Brazil, in a Children Education City Center (CMEI). Children ranging 5-6 years-old were evaluated by a neuropsychological assessment of voluntary activity and their teachers were interviewed. Data collected in Mexican school, where role play is structured by the teacher as a ‘principal activity’ pointed out that voluntary activity increased among the three groups assessed, as follows: as language passed from external to internal level; the initiative/independence increased by the introduction of symbolism in games; the decreasing of the level of distraction, which ensured the respect for regulations until the game ended; as children were capable of accomplishing actions that they were not out of the role play, for instance, the conflict resolution. On the other hand, in CMEI we observed the initial development of role play organized by children with no-structuring from the adult, despite of detecting voluntary activity indicators during the game. In this case, the indicators were unsatisfactory once we could perceive independence/initiative in some situations but also strictly attachment to objects, low use of verbal language and incapacity of solving conflicts. In view of this situation, the researcher conducted some specific interventions during games, attempting to operate on the ‘zone of proximal development’, and allowing the experiment of voluntary behaviors as well as progress in the way children organized games, as: increasing the time of commitment and the number of characters; exploring and sustaining a dialogue; exploring further possibilities of thematic; creating rules and solving conflicts according to social roles. Thus, we conclude that the social role play, intentionally organized by the teacher, promoted a greater number of actions indicative of voluntariness and with greater complexity, when compared to the role play without adult participation.